System and method for carbon capture and utilization - Vyrides, Ioannis (My University, 2025)
A system and a method for converting captured carbon dioxide (CO2) into hydrogen (H2) by using metallic iron or metallic magnesium in anaerobic process are described. In a first step, the CO2 can be absorbed in an alkaline solution such as NaOH and a soluble bicarbonate is formed. In a second step, the soluble bicarbonate HCO3- is converted into H2 by reacting it with zero valent metal, like metallic Fe (powder) or scrap Fe or Magnesium ribbon in anaerobic ambient conditions. Metal carbonate, like siderite, is created on the outer surface of Fe(0) and can be separated by the alkaline solution, which is recycled in the first reaction to be used for CO2 absorption. Exposing the separated siderite to weak acid, either citric acid or oxalic acid, zero valent metal is obtained, which is recycled in the second reaction. Alternatively, the siderite can be used as a raw material in the steel industry or cement industry or commercialized as an iron scrap. The generated H2 can be directly used for energy purposes or can be directed to another reactor comprising also bicarbonate solution and mix hydrogenotrophic methanogens to be converted into methane (CH4) or to a bioreactor comprising homoacetogenic bacteria to be converted into carboxylic acids, like acetic acid (CH3COOH). Alternatively, the reaction with Fe(0) or Mg(0), bicarbonate solution, CO2 and hydrogenotrophi
Keywords: CO2 capture; B01D53/62, C01B3/08, C01B32/60, C12P5/023, Y02C20/40, Y02E60/36; H2 production; Zero-Valent Metal